2014
DOI: 10.1523/jneurosci.2826-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Calcium Controls the Expression of Two Different Forms of Ripple-Like Hippocampal Oscillations

Abstract: Hippocampal high-frequency oscillations (HFOs) are prominent in physiological and pathological conditions. During physiological ripples (100 -200 Hz), few pyramidal cells fire together coordinated by rhythmic inhibitory potentials. In the epileptic hippocampus, fast ripples (Ͼ200 Hz) reflect population spikes (PSs) from clusters of bursting cells, but HFOs in the ripple and the fast ripple range are vastly intermixed. What is the meaning of this frequency range? What determines the expression of different HFOs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 96 publications
7
53
0
Order By: Relevance
“…Meanwhile, Ca 2ϩ regulates synaptic release and numerous other functions. Ca 2ϩ , like other divalent cations, also modulates disynaptic transmission by affecting spike threshold, which has recently been shown to modulate in vitro ripples (Aivar et al, 2014). Thus, an important goal of the present study was to compare ripples observed in in vitro slice experiments with ripples in the intact drug-free brain.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Meanwhile, Ca 2ϩ regulates synaptic release and numerous other functions. Ca 2ϩ , like other divalent cations, also modulates disynaptic transmission by affecting spike threshold, which has recently been shown to modulate in vitro ripples (Aivar et al, 2014). Thus, an important goal of the present study was to compare ripples observed in in vitro slice experiments with ripples in the intact drug-free brain.…”
Section: Discussionmentioning
confidence: 98%
“…Intracellularly recorded action potentials in the drug-free intact animal offered the opportunity to test the hypothesis that spikes during ripples invade the soma antidromically from the postulated gap junction-connected axonal nets (Schmitz et al, 2001;Bähner et al, 2011;. Action potential waveforms during ripples and outside ripples (excluding burst spikes) were both found to be orthodromic ( Fig.…”
Section: Characteristics Of Pyramidal Neuron Action Potentials Duringmentioning
confidence: 99%
See 1 more Smart Citation
“…This moment was also marked by the onset of HFOs in the LFP; 4) compared to the SWR-generating state, the cellular excitability increased and excitatory transmission was enhanced, whereas inhibitory transmission (both somatic and dendritic) was compromised; 5) additionally, a strong short-term depression was also observed in the PVBC to PC transmission. Aivar et al (201 4) [64] induced similar transitions from healthy to pathological forms of ripples by decreasing [Ca2+]e. They found similar shifts in excitability parameters and transmission parameters and concluded, similarly, that failure of inhibition results in strong PC firing that shapes the fRIPs. The importance of PVBCs in seizure propagation has been recently demonstrated [65].…”
Section: Generation Of Interictal Spikes: Changes In Cellular and Netmentioning
confidence: 93%
“…These findings explain Bragin et al's [1 6] original observation and support the consensus on RIP and fRIP generation [5, 8,[52][53][54] by showing that the LFP is dominated by inhibitory synaptic currents during SWRs [61 ] and by PC action potentials during IISs [60]. When inhibition fails during IIS, the balance is tipped in the same direction by the two counteracting mechanisms; on one side, the inhibitory synaptic currents disappear, while on the other side pyramidal cells start to fire en mass and the population spikes of their APs form the LFP signal of fast ripples (see also [64] fig 9). Fast ripples thus appear when and where inhibitory control is lost and massive PC firing erupts [71 ].…”
Section: Generation Of Interictal Spikes: Changes In Cellular and Netmentioning
confidence: 99%